Building a national brand for Vietnamese culture: Leadership as an art inspired by Max Depree - Ngoc, Truong Thi Minh; Novak, Marko (Edelweiss Applied Science and Technology, 2025)
This paper explores how Max DePree’s leadership philosophy, emphasizing vision, core values, and servant leadership, relates to Vietnam’s national identity, which has been profoundly shaped by the country’s historical experiences, including colonialism, war, economic reform, and global integration. A qualitative review of nation-branding literature, analysis of DePree’s theory, and case studies of Vietnamese cultural initiatives are combined with an assessment of policy frameworks and financial considerations to evaluate current practices and identify gaps. The study reveals that Vietnam’s cultural branding efforts are fragmented due to decentralized leadership, limited community participation, and weak coordination among governmental, private, and cultural stakeholders. These challenges hinder the development of a cohesive national cultural brand capable of supporting sustainable development and soft power objectives. A centralized, participatory leadership model, cross-sectoral collaboration, and strategic investment are essential to integrating Vietnam’s heritage and contemporary creativity into a compelling national brand. This research provides a roadmap for policymakers and cultural leaders to position Vietnam’s heritage and innovation as drivers of international influence and long-term economic and cultural sustainability.